2021
DOI: 10.1186/s12866-021-02133-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of carbapenem resistant Gram‐negative bacilli isolates recovered from hospitalized patients at Soba University Hospital, Sudan

Abstract: Background Antimicrobial resistance (AMR) poses a complex threat to global health security and universal health coverage. Recently, nosocomial infections with carbapenemase-producing Gram-negative bacilli (GNB) is increasing worldwide. We report the molecular characterization and detection of genes associated with carbapenemase producing Gram negative bacteria isolated from hospitalized patients at Soba University Hospital (SUH) in Khartoum State, Sudan. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
4
18
2
2
Order By: Relevance
“…However, it is very likely that the existence of only one carbapenem-resistance gene is not necessary associated with carbapenem-resistance. Contrary to what was previously noted in a study performed in Sudan, which revealed that 83% of isolates were positive by phenotypic tests, while 58.7% had one or more carbapenem-resistance genes [ 27 ].…”
Section: Discussioncontrasting
confidence: 73%
“…However, it is very likely that the existence of only one carbapenem-resistance gene is not necessary associated with carbapenem-resistance. Contrary to what was previously noted in a study performed in Sudan, which revealed that 83% of isolates were positive by phenotypic tests, while 58.7% had one or more carbapenem-resistance genes [ 27 ].…”
Section: Discussioncontrasting
confidence: 73%
“…Regarding blaVIM-2, the frequency was only 10.8 % (12/111) of the CR GNB isolates. This low rate is consistent with the research of Elbadawi et al [36] but differs from previous studies that showed a higher prevalence of this gene (82 %) [37]. We reported a low prevalence of blaSPM-1 and blaSIM-1 in this study (3.6 % and 1.8 % respectively) which agreed generally with previous studies but with different percentages (1.75% [38] and 4% [39] respectively.…”
Section: Discussionsupporting
confidence: 90%
“…MDR strains were defined based on the previous descriptions [ 13 , 14 ]. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion method under the requirement of the Clinical and Laboratory Standards Institute (CLSI) guidelines [ 15 ].…”
Section: Methodsmentioning
confidence: 99%